Enhanced magnetic parameters in the morphotropic phase boundary region of nanocrystalline multiferroic Bi1-xLaxFeO3 - Thakuria, P.; Joy, Pattayil Alias (Solid State Communications, 2012)
Antiferromagnetic multiferroic BiFeO3 shows ferromagnetic characteristics by simultaneous substitution of Bi by La and decrease in the particle size to nanometer dimensions. Large changes in saturation and remnant magnetization, magnetic susceptibility at low and high fields, along with some anomalous changes in the magnetic transition temperature are observed in nanocrystalline Bi1-xLaxFeO3 system for 0.1 <= x <= 0.2. This compositional region corresponds to the morphotropic phase boundary (MPB) region separating the rhombohedral and orthorhombic phases, and the effect is similar to that observed in many ferroelectric systems. The present observation of enhanced ferromagnetic parameters in the MPB region of the nanocrystalline multiferroic La substituted BiFeO3 system, combined with the known ferroelectric characteristics, is suitable for future device applications. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Bismuth ferrite; magnetic properties; Multiferroics; Nanocrystalline materials